Effect of sunflower seed oil emollient therapy on newborn infant survival in Uttar Pradesh, India: A community-based, cluster randomized, open-label controlled trial. - Aarti Kumar (Public Library of Science (PLoS), 2021)
Background Hospitalized preterm infants with compromised skin barrier function treated topically with sunflower seed oil (SSO) have shown reductions in sepsis and neonatal mortality rate (NMR). Mustard oil and products commonly used in high-mortality settings may possibly harm skin barrier integrity and enhance risk of infection and mortality in newborn infants. We hypothesized that SSO therapy may reduce NMR in such settings. Methods and findings This was a population-based, cluster randomized, controlled trial in 276 clusters in rural Uttar Pradesh, India. All newborn infants identified through population-based surveillance in the study clusters within 7 days of delivery were enrolled from November 2014 to October 2016. Exclusive, 3 times daily, gentle applications of 10 ml of SSO to newborn infants by families throughout the neonatal period were recommended in intervention clusters (n = 138 clusters); infants in comparison clusters (n = 138 clusters) received usual care, such as massage practice typically with mustard oil. Primary analysis was by intention-to-treat with NMR and post-24-hour NMR as the primary outcomes. Secondary analysis included per-protocol analysis and subgroup analyses for NMR. Regression analysis was adjusted for caste, first-visit weight, delivery attendant, gravidity, maternal age, maternal education, sex of the infant, and multiple births. We enrolled 13,478 (52.2% male, mean weight: 2,575.0 grams ± standard deviation [SD] 521.0) and 13,109 (52.0% male, mean weight: 2,607.0 grams ± SD 509.0) newborn infants in the intervention and comparison clusters, respectively. We found no overall difference in NMR in the intervention versus the comparison clusters [adjusted odds ratio (aOR) 0.96, 95% confidence interval (CI) 0.84 to 1.11, p = 0.61]. Acceptance of SSO in the intervention arm was high at 89.3%, but adherence to exclusive applications of SSO was 30.4%. Per-protocol analysis showed a significant 58% (95% CI 42% to 69%, p < 0.01) reduction in mortality among infants in the intervention group who were treated exclusively with SSO as intended versus infants in the comparison group who received exclusive applications of mustard oil. A significant 52% (95% CI 12% to 74%, p = 0.02) reduction in NMR was observed in the subgroup of infants weighing ≤1,500 g (n = 589); there were no statistically significant differences in other prespecified subgroup comparisons by low birth weight (LBW), birthplace, and wealth. No severe adverse events (SAEs) were attributable to the intervention. The study was limited by inability to mask allocation to study workers or participants and by measurement of emollient use based on caregiver responses and not actual observation. Conclusions In this trial, we observed that promotion of SSO therapy universally for all newborn infants was not effective in reducing NMR. However, this result may not necessarily establish equivalence between SSO and mustard oil massage in light of our secondary findings. Mortality reduction in the subgroup of infants ≤1,500 g was consistent with previous hospital-based efficacy studies, potentially extending the applicability of emollient therapy in very low-birth-weight (VLBW) infants along the facility-community continuum. Further research is recommended to develop and evaluate therapeutic regimens and continuum of care delivery strategies for emollient therapy for newborn infants at highest risk of compromised skin barrier function. Trial registration ISRCTN Registry ISRCTN38965585 and Clinical Trials Registry-India (CTRI/2014/12/005282) with WHO UTN # U1111-1158-4665.